Academic Resilience and Engagement in High School Students: The Mediating Role of Perceived Teacher Emotional Support - Luciano Romano; Giacomo Angelini; Piermarco Consiglio; Caterina Fiorilli (European Journal of Investigation in Health, Psychology and Education, 2021)
Academic resilience is the ability to overcome setbacks and chronic difficulties in the academic context. Previous studies have found that resilient students tend to be more engaged in school than their counterparts. Nevertheless, it seems worth deepening the role of contextual factors, such as teacher emotional support and how students perceive it, as it could contribute to foster the abovementioned relationship. The present study aimed to examine the links between academic resilience, perceived teacher emotional support, and school engagement. Moreover, the mediating role of perceived teacher emotional support was investigated. A sample of 205 Italian high school students (58.5% female), aged 14–19 years (M = 16.15, SD = 1.59), completed self-report questionnaires on academic resilience, perceived teacher emotional support, and school engagement. A structural equation model (SEM) was used to test the mediation hypothesis. The results showed that academic resilience was associated with perceived teacher emotional support, and both of them were related to school engagement. Furthermore, perceived teacher emotional support partially mediated the relationship between academic resilience and school engagement. Findings were discussed by underlining the importance of fostering personal and contextual resources in the school context to promote students’ well-being.